2008
DOI: 10.1002/pi.2422
|View full text |Cite
|
Sign up to set email alerts
|

UV‐curable, oxetane‐toughened epoxy‐siloxane coatings for marine fouling‐release coating applications

Abstract: BACKGROUND: UV-curable coatings are promising candidates for environmentally friendly marine foulingrelease coatings. Cationic UV-curable epoxy-siloxane release coatings show good release performance but suffer from poor coating mechanical properties. A difunctional oxetane monomer, DOX, was co-photopolymerized with an epoxy-siloxane oligomer at loading levels from 10 to 40 wt% to obtain toughened fouling-release coatings. RESULTS:The DOX-toughened coatings showed enhanced cationic photopolymerization activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…67 Finally, PDMS-epoxy pre-polymers were toughened by reacting with oxetane units (Fig. 68 The coatings containing 10 to 20% of oxetane showed a higher tensile modulus then the equivalent PDMS-epoxy resins, retained a low surface energy (o15 mN m À1 ), had a high CA and were stable upon immersion and water-jet washing with no signs of surface rearrangements. 68 The coatings containing 10 to 20% of oxetane showed a higher tensile modulus then the equivalent PDMS-epoxy resins, retained a low surface energy (o15 mN m À1 ), had a high CA and were stable upon immersion and water-jet washing with no signs of surface rearrangements.…”
Section: View Article Onlinementioning
confidence: 99%
“…67 Finally, PDMS-epoxy pre-polymers were toughened by reacting with oxetane units (Fig. 68 The coatings containing 10 to 20% of oxetane showed a higher tensile modulus then the equivalent PDMS-epoxy resins, retained a low surface energy (o15 mN m À1 ), had a high CA and were stable upon immersion and water-jet washing with no signs of surface rearrangements. 68 The coatings containing 10 to 20% of oxetane showed a higher tensile modulus then the equivalent PDMS-epoxy resins, retained a low surface energy (o15 mN m À1 ), had a high CA and were stable upon immersion and water-jet washing with no signs of surface rearrangements.…”
Section: View Article Onlinementioning
confidence: 99%
“…19,27,28 Coatings that were prepared in 24-well plates were inoculated with 1.0 mL of a suspension of N. incerta (10 5 cells/ mL) in F/2. The plates were incubated for 2 h under ambient conditions.…”
Section: Navicula Incerta Attachment and Adhesionmentioning
confidence: 99%
“…The objective of the research was to explore the feasibility of producing environmentally friendly antimicrobial, UV‐curable coatings that do not leach toxic materials to the environment. To determine if the coatings release toxic compounds, a leachate toxicity assay was conducted 17, 18. The results of this assay (data not shown) indicated that none of the coatings released toxic components.…”
Section: Resultsmentioning
confidence: 99%
“…that could potentially leach out and interfere with the biological assays designed to specifically characterize the antimicrobial properties of the coating surfaces 16. A leachate toxicity assay, which has been previously described in detail,17, 18 was used to verify that no toxic components were leaching from the coatings after the 14 days of water immersion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation